2001
DOI: 10.1152/ajplung.2001.281.2.l377
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol ingestion potentiates TNF-α-mediated oxidative stress and apoptosis in rat type II cells

Abstract: In septic patients, chronic alcohol abuse increases the incidence of the acute respiratory distress syndrome (ARDS). Because alveolar type II cell viability is critical for epithelial repair, our objective was to determine if chronic ethanol ingestion increased the sensitivity of type II cells to the inflammatory mediators upregulated during sepsis. In rats chronically fed ethanol, type II cell mitochondrial GSH was depleted, and tumor necrosis factor-alpha (TNF-alpha)-induced generation of mitochondrial react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 45 publications
(74 reference statements)
7
89
3
1
Order By: Relevance
“…The exact mechanism of this alcohol-related immunosuppressive effect is not clear but we suspect that ethanol may have a direct effect on lung epithelial cells, particularly ATII cells and Clara cells. For example, Brown et al have previously shown that chronic ethanol ingestion potentiates apoptosis of ATII cells in rats (Brown et al, 2001). The results of this experiment suggest that chronic ethanol exposure decreases the bioavailability of glutathione (GSH) to mitochondria of ATII cells.…”
Section: Discussionmentioning
confidence: 68%
“…The exact mechanism of this alcohol-related immunosuppressive effect is not clear but we suspect that ethanol may have a direct effect on lung epithelial cells, particularly ATII cells and Clara cells. For example, Brown et al have previously shown that chronic ethanol ingestion potentiates apoptosis of ATII cells in rats (Brown et al, 2001). The results of this experiment suggest that chronic ethanol exposure decreases the bioavailability of glutathione (GSH) to mitochondria of ATII cells.…”
Section: Discussionmentioning
confidence: 68%
“…Zinc also plays a role in the regulation of cellular glutathione (29) and protects cell membranes from oxidative damage (30). This is particularly intriguing, as we have published extensively on the role of oxidant stress and glutathione depletion in experimental models of chronic alcohol ingestion and in human subjects with alcohol abuse (5,7,(31)(32)(33)(34). Therefore, alcohol-induced zinc deficiency may play a central role in the oxidant stress and consequent cellular dysfunction that has been shown to characterize the alcoholic lung phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of chronic ethanol ingestion, this altered GSH homeostasis in the ELF (14) resulted in increased susceptibility to sepsis-induced acute lung injury as well as impaired alveolar type II cell function and viability (1,5,12). An important role for GSH availability as a predisposing factor to the development of acute lung injury was demonstrated by the ability of GSH precursors to attenuate injury in the rat model (4,5,14).Since alveolar macrophage are dependent on GSH in the ELF, and chronic alcohol decreases this GSH pool, we hypothesized that alcohol-induced macrophage dysfunction was secondary to alcohol-induced decreased GSH availability in this extracellular pool. Thus maintenance of GSH in the ELF during chronic ethanol ingestion should protect against the ethanol-induced decreases in macrophage phagocytosis.…”
mentioning
confidence: 99%